Advanced control strategies of VSC Based HVDC transmission system: Issues and potential recommendations - Hannan M.A.; Hussin I.; Ker P.J.; Hoque M.M.; Hossain Lipu M.S.; Hussain A.; Rahman M.S.A.; Faizal C.W.M.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Energy transfer; HVDC power transmission; Transmissions; Control strategies; Converter; HVDC transmission; line commuted converter; Voltage source converters; Electric power system control